Photoinduced charge transfer interaction between citrus limon extract passivated colloidal CdS with Methyl Violet & Beta Vulgaris dyes. (2021) - Panda, S.; Sahu, A.; Patra, A.; Panda, S.; Nahak, B.K.; Patra, B.N.; Mahato, S.S.; Mahata, S.
Highlights: As far as best of the knowledge, this is the first report on development CdS QD's using citrus limon extract. Photo induced charge transfer interaction of CdS QDs with two different dyes are noticeably different. Beta vulgaris dye shows H-aggregation on CLE capped CdS QD surface. Photo induced quenching of dyes is attributable to the e - transfer from dye to colloidal CdS. Abstract: Recently, use of different plant extracts for the green synthesis of CdS nanoparticles has appealed significant attention throughout the world. The components contained in antioxidant rich citrus fruits e.g. orange and lemon have attracted significant attention due to their chemical and biological properties. To date, the the synthesis of CdS nanoparticles using citrus limon extract as a surface functionalizing agent has not been explored. In the present study a reliable green synthesis method was developed by introducing Citrus Limon Extract (CLE) as a new surface functionalizing agent for the development of colloidal CdS quantum dots (CCQDs). Photo induced interaction between CLE functionalized colloidal CdS quantum dots with Methyl Violet (MV) & Beta Vulgaris (BV) dyes have been explored. Dyes adsorption on CdS surface results in quenching of dye molecules emission intensity. UV–Visible spectroscopic studies evidently reveal idiosyncratic photo-induced charge transfer interaction of CdS QDs with Methyl Violet (MV) dye noticeably differs from its interaction with Beta Vulgaris (BV) dye. Beta vulgaris dye shows H-aggregation on CLE capped CdS QD surface. Photo-induced quenching of both the dyes attributed to electron (e - ) transfer to the conduction band (CB) of CdS from the excited state of the dyes.